2023
DOI: 10.1002/clc.23970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia and its association with clinical outcomes in heart failure: An updated meta‐analysis and systematic review

Abstract: Background Sarcopenia is thought to be strongly associated with heart failure, but meta‐analyses with sufficient samples are still lacking to accurately address its clinical situation.Hypothesis: Sarcopenia has a high prevalence in patients with heart failure and is closely related to adverse clinical outcomes. Methods Relevant databases were systematically searched in October 2021 and updated in July 2022. The data with high heterogeneity were combined with random effects model. Results Twenty‐one studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
0
14
0
3
Order By: Relevance
“…Currently, the potential mechanisms underlying the association between reduced HGS and poor prognosis of patients with HF may be multifactorial. Previous studies showed that both sarcopenia 35 and frailty 36 are established predictors of poor prognosis in patients with HF. Reduced HGS as a reflection of muscle wasting in patients with HF has been involved as an important component for both sarcopenia and physical frailty, which may at least partly explain the prognostic role of HGS in these patients 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the potential mechanisms underlying the association between reduced HGS and poor prognosis of patients with HF may be multifactorial. Previous studies showed that both sarcopenia 35 and frailty 36 are established predictors of poor prognosis in patients with HF. Reduced HGS as a reflection of muscle wasting in patients with HF has been involved as an important component for both sarcopenia and physical frailty, which may at least partly explain the prognostic role of HGS in these patients 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that both sarcopenia 35 and frailty 36 are established predictors of poor prognosis in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with data showing an elevated prevalence of sarcopenic obesity in HF [ 24 , 25 ]. In a recent study, Chen et al examined the prevalence of sarcopenia in patients with HF and its association with adverse clinical outcomes and found that the overall prevalence of sarcopenia was 31%, and 18% in HF with preserved ejection fraction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a skeletal muscle disorder associated with age‐related loss of muscle mass and function, resulting in increased functional decline, mortality, and other adverse events, 1–3 and is closely associated with heart failure. In a recent meta‐analysis of patients hospitalized with heart failure, the prevalence of sarcopenia was estimated at 35–55% 4,5 . Heart failure is subject to sarcopenia evaluation according to the Asian Working Group for Sarcopenia (AWGS) 2019 algorithm 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta‐analysis of patients hospitalized with heart failure, the prevalence of sarcopenia was estimated at 35–55%. 4 , 5 Heart failure is subject to sarcopenia evaluation according to the Asian Working Group for Sarcopenia (AWGS) 2019 algorithm. 6 Sarcopenia guidelines currently recommend dual‐energy X‐ray absorptiometry (DEXA) or bioelectrical impedance analysis (BIA) for diagnosing low appendicular skeletal muscle mass (ASM) in Asians and Europeans.…”
Section: Introductionmentioning
confidence: 99%